Prevalence and antimicrobial resistance patterns of methicillin-resistant staphylococci (MRS) isolated in a Veterinary Teaching Hospital in Brazil - Maluta, Renato Pariz [UNESP]; Stella, Ariel Eurides [UNESP]; Rigobelo, Everlon Cid [UNESP]; Oliveira, Ana Claudia de [UNESP]; Franco Lemos, Manoel Victor [UNESP]; Ávila, Fernando Antonio de [UNESP] (Academic Journals, 2010)
We investigated the prevalence of methicillin-resistant staphylococci (MRS) in humans and dogs and evaluated the antimicrobial resistance patterns of these bacteria at a Veterinary Teaching Hospital. Specimens from 50 human subjects and 50 dogs were studied. Isolates were identified by Gram-staining, biochemical reactivity and resistance to antimicrobials. While no isolates of methicillin-resistant Staphylococcus aureus (MRSA) or methicillin-resistant Staphylococcus intermedius (MRSI) were isolated, two (4%) methicillin-resistant coagulase-negative staphylococci (MRCoNS) were isolated from dogs and 18 (36%) were isolated from humans. The percentage of MRCoNS isolates resistant to penicillin (100%), ciprofloxacin (30%), gentamicin (40%), clindamycin (25%), erythromycin (70%), trimethoprim-sulfamethoxazole (20%) or vancomycin (0%) was evaluated. The absence of MRS isolates resistant to vancomycin is of interest because this antimicrobial may be used as an important therapeutic alternative in cases of MRSA infections. Surveillance programs aimed against MRS should therefore be stimulated in veterinary health units.
Keywords: Dog; MRS; nosocomial; Veterinary staff